Differences in mortality risk by levels of physical activity among persons with disabilities in South Korea - Lee SeungCheor; Lee Yeowool; Park Saengryeol; Park So-Youn; Oh In-Hwan (Open Medicine)
The World Health Organization’s recommendation of at least 150 min of physical activity per week is important for increasing the lifespan of persons with disabilities (PWDs).